Resolution and shape in bioprinting : strategizing towards complex tissue and organ printing - Lee, Jia Min (2019)
In 3D bioprinting, printing resolution represents the deposited material in the x- and y-axes, while dimensionality defines the structural resolution of printed constructs. Dimensionality in 3D bioprinting can be defined as the resolution in the z-axis. The printing resolution, together with dimensionality, contributes to the overall shape fidelity of the bioprinted constructs. The in-depth understanding of physical processes for different printing technologies is imperative in controlling the print resolution and definition. In this article, bioprinting technologies are classified according to the physical processes that deposit or form the bioprinted construct. Due to the different fabrication processes in forming fundamental printed units (voxels), the definition of printability differs for each bioprinting technique. Another aspect of resolution is the spatial positioning of cells within each fundamental building unit. The proximity of cells in the bioprinted construct affects the physiological outcomes. The second aspect of 3D bioprinting technologies is the ability to control shape fidelity. Different strategies have been used to improve the construction of a 3D engineered tissue or organ. Lastly, moving toward complex tissue printing involves adding functionalities to the bioprinted construct. Data processing, material formulations, and integration of different fabrication technologies are key areas in bioprinting that can recapture the different hierarchical aspects of native tissues. This article presents a comprehensive overview of enhancing the resolution of the bioprinting construct and identifying methods to improve functionalities of bioprinted tissues.